The elusive crystals of calcium acetate hemihydrate: chiral rods linked by parallel hydrophilic strips. Issue 3 (16th December 2020) - Abrahams, Brendan F.; Commons, Christopher J.; Hudson, Timothy A.; Sanchez Arlt, Robin W.
Abstract : The chance discovery of crystals of calcium acetate hemihydrate, which is commonly formed on calcareous heritage objects, has allowed its single crystal structure determination; this remarkable crystal structure consists of chiral rod-like units. Abstract : Calcium acetate hemihydrate is found in the efflorescent salts that form on pottery and other calcareous heritage artefacts. The formation of these salts can lead to deterioration of these objects. A recent analysis of the structure of Ca(OAc)2 ·½H2 O by X-ray powder diffraction (XRPD) has revealed it has a remarkable and surprisingly complex structure. Although the compound usually exists in powder or microcrystalline form, often in mixtures with other salts, we have serendipitously managed to grow crystals of a size suitable for single crystal X-ray diffraction. Our single crystal data show the structure is based on infinite supramolecular polymeric rods that are chiral. Each rod has a minimum diameter of 1.75 nm and the external surface of each rod features four parallel, hydrophobic domains separated by hydrophilic strips. Each hydrophilic strip consists of acetate oxygen atoms and coordinated water molecules that are able to form hydrogen bonding interactions with symmetry-related strips on a neighbouring rod in an arrangement that resembles a zipper. Within the extended crystal structure each rod is bound to four rods of opposite handedness to give a racemic mixture.